2017
DOI: 10.1523/eneuro.0339-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Shaping of Signal Transmission at the Photoreceptor Synapse by EAAT2 Glutamate Transporters

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 59 publications
1
39
0
Order By: Relevance
“…We used bacterial artificial chromosome (BAC)-recombineering to generate an slc1a2b fluorescent reporter line, TgBAC(slc1a2b:Citrine), expressing Citrine in the cytoplasm of RG ( Figure 1d and Figure S1) (Bussmann & Schulte-Merker, 2011). In slc1a2b:Citrine zebrafish, the fluorescent expression pattern appeared highly similar to that observed by slc1a2b mRNA in situ hybridization, showing cell bodies lining the ventricle and radial fibers extending throughout the brain (Figure 1d and Figure S1) (Franceschi et al, 2018;Gesemann, Lesslauer, Maurer, Schonthaler, & Neuhauss, 2010;McKeown et al, 2012;Niklaus et al, 2017;Rohrschneider, Elsen, & Prince, 2007). We next visualized lysosomes in RG of control and hexb crispants.…”
Section: Direct Mutagenesis Causes Hexb Enzyme Deficiency and Glialmentioning
confidence: 76%
“…We used bacterial artificial chromosome (BAC)-recombineering to generate an slc1a2b fluorescent reporter line, TgBAC(slc1a2b:Citrine), expressing Citrine in the cytoplasm of RG ( Figure 1d and Figure S1) (Bussmann & Schulte-Merker, 2011). In slc1a2b:Citrine zebrafish, the fluorescent expression pattern appeared highly similar to that observed by slc1a2b mRNA in situ hybridization, showing cell bodies lining the ventricle and radial fibers extending throughout the brain (Figure 1d and Figure S1) (Franceschi et al, 2018;Gesemann, Lesslauer, Maurer, Schonthaler, & Neuhauss, 2010;McKeown et al, 2012;Niklaus et al, 2017;Rohrschneider, Elsen, & Prince, 2007). We next visualized lysosomes in RG of control and hexb crispants.…”
Section: Direct Mutagenesis Causes Hexb Enzyme Deficiency and Glialmentioning
confidence: 76%
“…This depolarization could be largely suppressed by 1 μM (2S, 3S)-3-[3-[4-(trifluoromethyl) benzoylamino]benzyloxy]aspartate (TFB-TBOA) (15.2% ± 3.1% of control, p < 0.01), a selective inhibitor of subtypes 1 and 2 of the excitatory amino acid transporters EAAT1 and EAAT2 (also called glutamate and aspartate transporter [GLAST] and glutamate transporter [GLT]-1, respectively) (Tsukada et al, 2005). Previous studies showed that in larval zebrafish, EAAT2 but not EAAT1 was consistently found to be expressed in the retina (Gesemann et al, 2010; Niklaus et al, 2017) and that both EAAT2a and 2b subtypes are expressed in MGCs but not in RGCs (Niklaus et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Under physiological conditions, glutamate is released in the synapses and subsequently taken up by excitatory amino acid transporters (EAATs) of mainly Müller glial cells but also other cell types, preventing excitotoxic concentrations. In the outer retina, extracellular glutamate is mainly transported into Müller cells through EAAT1/GLAST, but EAAT2/GLT-1 on glial and non-glial cells also contributes to glutamate recapture [32]. After the uptake of extracellular glutamate by Müller cells, intracellular glutamate can be released from glial cells by a cystine/glutamate antiporter, the x c − system, to import cystine to fuel glutathione synthesis necessary for anti-oxidant defense [33].…”
Section: Il-1β Disrupts Glutamate Homeostasis In Müller Glial Cellsmentioning
confidence: 99%